CORRUPTION: NOT A TABOO FOR INDONESIANS? - Ahmad Syauki; Muhammad Iqbal Fasa; Suharto; Adib Fachri (Kajian Hukum, 2022)
The problem of corruption has never been separated from human life from ancient times until now. Corruption is a social disease that will cause an opium effect for the perpetrators. In addition to harming the country, corruption is also self-defeating because if someone is already entangled in corrupt behavior, he will continue to do so until one day his actions are known to the authorities. The author wants to open people's minds about corruption and corrupt behavior so that it is hoped that it will make readers aware that corruption is not a behavior that should be proud of. Data shows that corruption cases in Indonesia are dominantly increasing every year and this is not good news. The data also shows that from 2004-2018 only a handful of corruption cases in Indonesia were able to reach the courts, this means that the Corruption Eradication Commission (KPK) seems overwhelmed in handling these cases. Apart from repressive measures, preventive measures such as early anti-corruption education must also be taken to break this vicious circle. This work is using normative juridical method through a rule of law, case, and conceptual approach. Keywords: Corruption, Law, Human Character, Corruptive Behavior, Indonesia.